INVESTIGATION OF INTERDISCIPLINARY APPROACHES IN SECONDARY-LEVEL ENGLISH GRAMMAR INSTRUCTION, FOCUSING ON THE TEACHING OF VERB TENSES - Begmatov, Azizbek (University Research Base, 2024)
This paper explores the application of interdisciplinary thinking patterns in the teaching of English verb tenses at the secondary level. By integrating grammar instruction with subjects like history, science, literature, and mathematics, the paper highlights how students can gain a deeper understanding of tense usage. Interdisciplinary approaches allow students to move beyond memorization, enabling them to grasp the abstract concept of time more intuitively and apply verb tenses accurately in various contexts. The study emphasizes the benefits of critical thinking, problem-solving, and collaborative learning in making grammar instruction more dynamic and relevant. Ultimately, this approach fosters both language proficiency and cognitive development, preparing students for effective communication across disciplines.